(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
This article provides an overview of the newest mobile health apps based on Internet of Things that are utilized for diabetes control. Diabetic is a group of metabolism illnesses characterized by persistently increased glucose content. Long-term hyperglycemia management requires the involvement of individuals, doctors, and familial careers. With rapid advancements in cellular and network technologies, a range of World wide web of Things-based solutions for diabetic’s management have already been proposed. The majority of these apps are focused on medical observation and technology-assisted selection. We look at how these new applications work and their basic technology, as well as the major issues and difficulties they face. The major goal of this paper is to aid academics in the development of better diabetic management applications.